(untitled) (International Journal of Food and Nutritional Sciences, 2023)
This research paper examines the intricate relationship between training design and employee performance, with a particular emphasis on how this relationship is influenced by gender and age. Utilizing descriptive statistics and independent sample t-tests, the study analyzes data from a diverse group of employees across various industries.